Pengelolaan Keuangan dan Kompetensi Sumber Daya Manusia terhadap Kinerja Jasa Konsultan Kontruksi Di Kota Padang - Eka Rosalina Rosalina (Politeknik Negeri Padang, 2021)
To produce good performance, construction consulting service business actors must know how to managetheir business finances. A construction consultant service business with good performance will have highcompetitiveness. To make this happen, qualified human resources are needed. This study aims to explore theinfluence of financial management and human resource competence on the performance of constructionconsulting services. The population in this study were all construction consultant service owners in PadangCity who were registered in INKINDO West Sumatra and PERKINDO West Sumatra. This study used 111samples using the Slovin formula in determining the number of research samples and the sampling techniqueused was simple random sampling. The data collection technique was carried out by distributingquestionnaires to all construction consultant service owners. To answer the research hypothesis usinganalysis tools, namely multiple linear regression. The results showed that financial management had apositive effect on the performance of construction consulting services, while human resource competence hadno effect on the performance of construction consulting services